2020
DOI: 10.1177/0363546520969973
|View full text |Cite
|
Sign up to set email alerts
|

The Statistical Fragility of Hamstring Versus Patellar Tendon Autografts for Anterior Cruciate Ligament Reconstruction: A Systematic Review of Comparative Studies

Abstract: Background: Evidence-based medicine utilizes data to inform clinical decision making, despite the ability of a small number of outcome reversals to change statistical significance. P values are common measurements of statistical significance that possess inherent flaws. The inclusion of the fragility index (FI) and fragility quotient (FQ) may provide a clearer conveyance of statistical strength. Purpose/Hypothesis: The purpose was to examine the statistical stability of studies comparing hamstring tendon and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 52 publications
5
21
0
Order By: Relevance
“…However, this study had a very large patient population compared with the average orthopaedic study, with 5540 patients. By dividing the FI by the 5540 patients included in this population database study, Ehlers et al 9 found an FQ of 0.021, which is more consistent with the average FQ reported in orthopaedic literature (0.036) and in this study (0.043). This example highlights how FI can be misinterpreted when used on its own.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, this study had a very large patient population compared with the average orthopaedic study, with 5540 patients. By dividing the FI by the 5540 patients included in this population database study, Ehlers et al 9 found an FQ of 0.021, which is more consistent with the average FQ reported in orthopaedic literature (0.036) and in this study (0.043). This example highlights how FI can be misinterpreted when used on its own.…”
Section: Discussionsupporting
confidence: 90%
“…For this review, the median FI was found to be 2, and the median FQ was 0.035, which is consistent with previous orthopaedic literature reporting an average median FI of 3.67 ¶ and FQ of 0.036. 9 , 19 , 27 , 35 37 , 45 This study’s findings demonstrated that statistical significance can be changed with <3 outcome reversals, or reversal of 3.4% of outcome events. Furthermore, 13 of the 16 significant outcomes (81%) reported needed just a single outcome reversal to become statistically nonsignificant.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations